Residents’ Perception of Enviromental Impacts of Tourism Recretional Activities in Protected Area - SHARMA, Ravi; CHAURASIA, Sushil; BHATTACHARYA, A.K. (Journal of Environmental Management and Tourism, 2016)
This paper aims to investigate the local perceptions of environmental impacts generated due to tourism activities. The data was collected through a pre-tested survey instrument for the impact indicators. Analysis of variance pairwise comparison test was used to analyze any significance difference among the respondents’ perception towards selected parameter of tourism impact based on location. The results indicate that the local communities have strong perceptions of the negative economic impacts of tourism although it is also represented that it is perceived in a speculative way by those who do not have direct contact with the tourism destination.
Keywords: perception; environmental impact; tourism; residents’; impact category